1999
DOI: 10.2343/geochemj.33.167
|View full text |Cite
|
Sign up to set email alerts
|

REE partitioning between Fe-Mn oxyhydroxide precipitates and weakly acid NaCl solutions: Convex tetrad effect and fractionation of Y and Sc from heavy lanthanides.

Abstract: Distribution coefficients of Kd (REE: ppt./sol.) with REE = lanthanides (Ln), Y, and Sc between Fe Mn oxyhydroxide precipitates and NaCI solutions have been determined in pH = 5.4-6.4 at room tempera ture and atmospheric pressure. The logKd(Ln) values show convex tetrad effect variations across the series and positive Ce anomalies. Kd(Y) values are significantly lower than those for Ho and Er, whereas Kd(Sc) values are higher than those for Lu. Behaviors of Y3+ and.Sc3+ are distinct from heavy Ln3+ when REE co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 31 publications
(38 reference statements)
6
46
0
Order By: Relevance
“…All the variation patterns exhibit convex tetrad curves, small positive Ce anomalies, log K d (Y) smaller than log K d (Ho), and log K d (Sc) values much larger than those of the other REEs. These characteristics are in agreement with those reported by Bau (1999) and Kawabe et al (1999a …”
Section: Ree Partitioning Coefficients Between Fe Oxyhydroxide Precipsupporting
confidence: 83%
See 1 more Smart Citation
“…All the variation patterns exhibit convex tetrad curves, small positive Ce anomalies, log K d (Y) smaller than log K d (Ho), and log K d (Sc) values much larger than those of the other REEs. These characteristics are in agreement with those reported by Bau (1999) and Kawabe et al (1999a …”
Section: Ree Partitioning Coefficients Between Fe Oxyhydroxide Precipsupporting
confidence: 83%
“…(5) can be re-written in the form; log log , log log . Kawabe et al (1999a) suggested that REECl 2+ (aq) and REEOH…”
Section: Ree Partitioning Coefficients Between Fe Oxyhydroxide Precipmentioning
confidence: 99%
“…Figure 1, which is quoted from Kawabe et al (1999a) When all the logK d (org/aq) values are used in the least-squares fittings for both cases, the average errors of fittings are 0.09 for the system A and 0.05 for the system B in the logarithmic unit. However, when we exclude the logK d (org/aq) value only for La(III) in the system A, the average fitting error is reduced to be 0.06 from 0.09.…”
Section: Lanthanide Tetrad Effects In Solvent-extraction and Rspet Eqmentioning
confidence: 99%
“…These two terms can be written collectively, (9/13)n(S)C 1 Z* + m(L)C 3 Z* = {n(S) + (13/9)(C 3 /C 1 )m(L)}(9/13)C 1 Z*. (2) When it is assumed that (C 3 /C 1 ) = 0.21 as in Kawabe et al (1999a),…”
Section: Lanthanide Tetrad Effects In Solvent-extraction and Rspet Eqmentioning
confidence: 99%
“…Therefore, it is not unreasonable that the thermodynamic parameters for y3+ and H03+ are different in spite of their almost same ionic radii. Kawabe et al (1999) (Figs. 3(a), 3(b) and 4).…”
Section: Resultsmentioning
confidence: 99%